2015
DOI: 10.5958/0974-9357.2015.00120.8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment towards Nurses in Pakistan: Are we Safe?

Abstract: Background: Sexual harassment towards nurses has negative consequences, both for the nurses and for the health care organizations.Female nurses are more at risk for sexual violence because their caring a�itude is misperceived by male patients as sexual signals. This study aimed to explore the prevalence of sexual harassment towards nurses. Method:A descriptive Cross-sectional study was conducted with 458 registered nurses from all the Inpatient units and the Emergency departments of two government and two priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
4
12
0
Order By: Relevance
“…Although this study has not calculated a statistic significant value of women being more often exposed to SH the results are supported by previous studies (Bronner et al, 2003;Fute et al, 2015;K. Lee et al, 2007;Somani et al, 2015). In 2017, it was estimated by United Nation Women (2017) that 35% of all women worldwide have been exposed to either physical and/or sexual intimate partner violence or sexual violence by a non-partner.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although this study has not calculated a statistic significant value of women being more often exposed to SH the results are supported by previous studies (Bronner et al, 2003;Fute et al, 2015;K. Lee et al, 2007;Somani et al, 2015). In 2017, it was estimated by United Nation Women (2017) that 35% of all women worldwide have been exposed to either physical and/or sexual intimate partner violence or sexual violence by a non-partner.…”
Section: Discussionsupporting
confidence: 67%
“…Although women are the most common targets for sexual harassment, men can also be victims to SH, especially vulnerable groups such as “young men, gay men, members of ethnic or racial minorities, and men working in female-dominated work groups” (McCann, 2005). Despite an increase in male nurses and nursing studies, the nursing profession can still be seen as a feminine work due to its caretaking character and female nurses are more prone to be sexually harassed than male nurses (Bronner et al., 2003; Lamesoo, 2013; Somani et al., 2015; Spector et al., 2014).…”
Section: Sexual Harassment Workplaces and In Clinical Practicementioning
confidence: 99%
“…, Somani et al . ). None of this is conducive to nurses developing the confidence to speak out about what it is that nurses do and the differences nurses can make.…”
Section: Discussionmentioning
confidence: 97%
“…A previous concept analysis reported that negative images portrayed in the media influence nurses' reluctance to speak to the media (Rezaei-Adaryani et al 2012). Moreover, the gendered and aggressive tone of much of the newspaper and social media reporting and commentary on nursing resonates with reports of gendered, sexualised and demeaning verbal violence nurses experience in their workplaces (Jackson et al 2013, Spector et al 2014, Somani et al 2015. None of this is conducive to nurses developing the confidence to speak out about what it is that nurses do and the differences nurses can make.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual harassment: prevalence, types and consequences Sexual harassment has been defined as any "unwanted or unwelcome conduct of a sexual nature, in a workplace or in connection with work, which makes a protected person feel humiliated, intimidated, discriminated against or offended" (International Labour Organization, 2001) and is relatively frequent in health care settings (e.g. Çelik and Çelik, 2007;Somani et al, 2015;Wang, 2012). Although the estimated prevalence varies according to country, research methodology, and specific work setting, it has been estimated that one in four nurses are exposed to sexual harassment (Spector et al, 2014).…”
Section: Introductionmentioning
confidence: 99%